Literature of Reklam at Kurdish newspaper Descriptive search of Reklam in terms of language and the view (khabat newspaper 2005-2006) - Mohammed, Ariana I. (Humanities Journal of University of Zakho, 2014)
The art of advertising in the press work is important and necessary, one of the important activities that help media organizations to obtain funding necessary material for continuing to work and get their message across media, which began to appear in all its forms and developed according to historical stages of its progress, not the advertising industry of the arts developed, but is as old as history, has begun advertising on multiple forms evolved over the centuries until it became the art of advertising as we know it now, the Declaration is the art of well developed self-development technical we come to it, with great development wrought by technology in our world today, reflected in turn the world of advertising has become methods design of advertising and out of its development and a lot of gravity. The Declaration is therefore associated with a set forms and methods of multiple and varied, and through them processed and then displayed and published, so we have seen that it is necessary to the preparation of this research to identify the most important methods or styles of display ads and the most important types in terms of design and directed them. Find start talking about the concept of advertising and provides a simple definition of it then identifies the most important kinds of advertising in general, then presents the most important styles of directing and design of newspaper advertisements, and ends with the most important findings of the researcher and the list of references.